INFLUENCE OF HOST AND NON-HOST CELL WALLS ON THE INDUCTION OF CELL WALL DEGRADING ENZYMES IN VERTICILLlUM DAHLlAE - H. C. DUBE, G. S. PRASAD and (Indian Phytopathology, 2002)
Induction of cell wall degrading enzymes in cultures by Verticillium dahliae was examined in presence of host and non-host cell walls. Enzymes were produced in a temporal sequence on both types of cell walls. Pectic enzymes appeared first followed by hemicellulases and cellulase. Production of pectic enzymes was delayed in presence of non-host cell walls.